2016
DOI: 10.1155/2016/9232593
|View full text |Cite
|
Sign up to set email alerts
|

Genus Tinospora: Ethnopharmacology, Phytochemistry, and Pharmacology

Abstract: The genus Tinospora includes 34 species, in which several herbs were used as traditional medicines by indigenous groups throughout the tropical and subtropical parts of Asia, Africa, and Australia. The extensive literature survey revealed Tinospora species to be a group of important medicinal plants used for the ethnomedical treatment of colds, headaches, pharyngitis, fever, diarrhea, oral ulcer, diabetes, digestive disorder, and rheumatoid arthritis. Indian ethnopharmacological data points to the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 133 publications
(123 reference statements)
1
32
0
7
Order By: Relevance
“…Species of genus Tinospora are widely used as a folk medicine for various purposes [7] . Tinospora species have been reported to possess antidiabetic, antioxidant, immunostimulatory and antiosteoporosis activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Species of genus Tinospora are widely used as a folk medicine for various purposes [7] . Tinospora species have been reported to possess antidiabetic, antioxidant, immunostimulatory and antiosteoporosis activities.…”
mentioning
confidence: 99%
“…Further, Ayurveda has listed T. cordifolia in the management of diabetes. T. capillipes and T. sinensis are also offi cially listed in Chinese Pharmacopoeia [7,8] . Borapetoside C is one of the active phytoconstituents from T. crispa while cordifolioside A and magnofl orine are the major phytoconstituents from T. cordifolia and were reported to cause a reduction of oxidative stress and regularise carbohydrate metabolism [9][10][11] in experimental models of T2DM.…”
mentioning
confidence: 99%
“…Compound 45 produced its [M − H] − ion at m / z 597.20002 (C 28 H 37 O 12 S), which exhibited the characteristic fragment ion [M − H − C 8 H 14 O 6 S] − at m / z 359 suggesting the overall fracture of side chain. S-diterpenoids glycosides were very rare in Tinospora , and there only two compounds were reported in this family so far [ 30 ]. By comparison with the fragmentation pathways, compound 45 was plausibly described as cordifolide A.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been used for the management of asthma, migraine, piles, diabetes, etc., as a folk remedy in these countries (Baral & Kurmi, ; Saha & Ghosh, ). Moreover, this plant is also used as a general tonic, hepatoprotective, antiperiodic, antispasmodic, anti‐inflammatory, antiarthritic, and antiallergic (Chi et al, ; Singh & Chaudhuri, ). It has been reported that berberine, magnoflorine, tinosporine, cordifol, columbin, b‐sitosterol, and tinosporic acid have been isolated from T. cordifolia (Saha & Ghosh, ; Singh & Chaudhuri, ).…”
Section: Introductionmentioning
confidence: 99%